Immediate Effects of Walking Training With Elastic Ankle Support Devices on Walking and Mobility of Ambulatory Individuals With Stroke - Thaksin Chanata; Sugalya Amatachaya; Teerawat Nithiatthawanon; Jirabhorn Wannapakhe; Wannapai Chanwised; Arpassanan Wiyanad; Thiwabhorn Thaweewanakij; Wilairat Namwong (Annals of Rehabilitation Medicine, 2026)
Objective: To compare the immediate effects of walking training without or with an ankle support device (ASD) on spatiotemporal gait parameters, mobility, and satisfaction among 20 ambulatory participants with chronic stroke.Methods: This crossover design required the participants to complete the four 30-minute walking training conditions in a randomized order: without ASD, with ankle-foot orthosis (AFO), with long ankle sling made from 3- to 4-inch elastic bandage, and with elastic ankle support equipment (EASE) developed from elastic bands with buttonholes and plastic rivets, with a 7-day washout period. Gait parameters and Timed Up and Go test (TUG) were measured before and after each training program, and satisfaction with the three ASDs was assessed upon completion.Results: Spatiotemporal parameters (except walking cadence and symmetry) and TUG after training with a long ankle sling and EASE were significantly better than those following training without ASD and with AFO (p